Ovarian Follicular Growth And Embryonic Development In Rabbits Fed Palm Kernel Cake Based-Diet - Malahubban, Masnindah (2007)

(untitled)
An experiment was conducted to evaluate the effect of different diets on the follicular growth and embryo development in the female rabbits. Thirty - six adult rabbits (6-month-old) were randomly assigned into three dietary treatments namely Commercial rabbit pellet (Control); 50% Palm Kernel Cake (50%PKC) and PKC+ Ammonium Molybdate and Sodium Sulphate (PKC+MS) in an individual wire cage, and have access to water and feed ad-libitum for eight weeks prior to mating. The changes in body weight and feed intake were recorded weekly. All rabbits were sacrificed at the end of the experiment at different stages (prior to mating (n=2), within 5- 6 hours post mating (n=6) and at 48 hours after mating (n=4) from each treatment). Both ovaries from rabbits sacrificed prior to or within 5 – 6 hours post mating were prepared for serial sectioning and then stained using Haematoxylin and Eosin (H & E). Slides were examined under microscope (40X magnification) to identifiy and classifiy the follicles as either healthy or atretic, measured and either classified as small (<0.1 mm), medium (0.5 mm) and large (>1.0 mm) in diameter. Both oviducts from rabbits sacrificed 48 hours post mating were flushed with PBS supplemented with 10% inactivated fetal calf serum. Embryos were recovered, fixed and stained with Hoechst 33342 and examined under Fluorescent microscope for quality evaluation. Data were analysed using General Linear Model and Chi – square. The results from this study, showed that there were significant difference (P<0.05) in terms of feed intake and live bodyweight at 8 weeks, in all the dietary treatments and also there was a significant different in copper (Cu) concentration (P<0.05) in the liver, ovary and serum with high concentration of Cu in rabbits fed 50% PKC (31.93 ± 1.20 ppm, 5.36± 0.11 ppm, 1.63 ± 0.15 ppm respectively). However, addition of 0.22 g/kg sulphur dry weight and 0.0013 g/kg molybdenum dry weight to rabbits fed with PKC as basal diet could avoid Cu accumulation in serum, liver and ovary.The number of large follicles on the ovaries from rabbits fed on PKC+MS and Control diets were significantly higher (P<0.05) than from rabbits fed on 50% PKC. The numbers of healthy large and medium follicles were significantly higher (P<0.05) in Control and PKC+MS compared to 50% PKC. In general, most follicles in the ovaries from rabbits fed on 50% PKC were atretic in small (63%; n=109), medium (67%; n=36) and large (54%; n=24) compared to Control were atretic in small (33%; n=76), medium (26%; n=50) and large (20%;n=46) and also PKC+MS were atretic in small (24%; n=126), medium (30%; n=47) and large (21%; n=47). Although, there are not statisically significant between rabbits fed with three different dietary treatments in terms of embryo development, but number of corpus lutea and embryo were decreasing in rabbit fed with 50% PKC (8.2 ± 2.36%; 3.0 ± 0.82%; 37.5 ± 0.20%) compared to rabbits fed Control (10.0 ± 1.08%; 5.0 ± 0.82%; 50.6 ± 0.13%) and PKC+MS diets (10.8 ± 1.11%; 5.8 ± 1.31%; 53.4 ± 0.19%). There was significant difference (P<0.05) in the percentage of embryos at the early morula stage in rabbits under 50%PKC diet (16.7%; 2/12) as compared to Control (40%; 8/20) and PKC+MS diets (47.8%; 11/23).This study suggests that the accumulation of Cu in liver, ovary and serum of rabbits fed on 50% PKC diet were consumed less diet, reduced body weight, healty, medium and large number of follicles and also negative effect to the development embryo. However, PKC with Ammonium Molybdate and Sodium Sulphate, improved the development of follicle and embryo more compared to control dietary treatment. Therefore, having a balanced Cu content is an important aspect in reproduction.